Imaging of Airway Obstruction in Children - Derek J. Roebuck; Derek J. Roebuck; Conor Murray; Clare A. McLaren; Clare A. McLaren (Frontiers Media S.A., 2020)
Various imaging techniques may be used to diagnose airway obstruction in children. Digital radiography, computed tomography and magnetic resonance imaging are the most important modalities, but the choice of technique will depend on the level and nature of suspected obstruction, as well as patient-specific factors such as age and ability to cooperate. This review examines the forms of airway obstruction that are commonly encountered in childhood.